2022
DOI: 10.1016/j.diabres.2022.109227
|View full text |Cite
|
Sign up to set email alerts
|

Associations between depression and cognition, mild cognitive impairment and dementia in persons with diabetes mellitus: A systematic review and meta-analysis

Abstract: This systematic review aimed to examine whether persons with diabetes and depression had poorer cognition and higher dementia risk than persons with diabetes only. Moreover, the impact of timing, frequency of depressive episodes throughout life, and antidepressant treatment were examined. Methods: PubMed, Embase and PsycINFO were searched to obtain observational studies between August 2015 and June 2021 that examined the association between depression and cognition, mild cognitive impairment or dementia in peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 55 publications
3
26
0
1
Order By: Relevance
“…As per the meta-analysis of van Steenbergen-Weijenburg et al of 596 (63%) patients with T2DM in the outpatient clinic, patients with T2DM with two or more complications (OR: 2.23; 95% CI: 1.02-2.94), including neuropathy (OR: 1.7; 95% CI: 1.10-2.77) and nephropathy (OR: 1.68; 95% CI: 1.00-2.48), had more than twofold increase in the risk of depression [78]. Persons with depression in diabetes have poorer cognition and higher dementia risk than those with only diabetes, as evidenced by the study of Chow et al [79]. They performed an observational meta-analysis on 10 studies from August 2015 to June 2021 (six years) on the adult population and found that persons with comorbid diabetes and depression had worse cognition (SMD: -0.77 (-1.33, -0.20)) and greater dementia risk (HR: 1.82 (1.79, 1.85)) than persons with only diabetes [79].…”
Section: Effect Of Depression On Morbidity and Mortality In Diabetesmentioning
confidence: 90%
See 1 more Smart Citation
“…As per the meta-analysis of van Steenbergen-Weijenburg et al of 596 (63%) patients with T2DM in the outpatient clinic, patients with T2DM with two or more complications (OR: 2.23; 95% CI: 1.02-2.94), including neuropathy (OR: 1.7; 95% CI: 1.10-2.77) and nephropathy (OR: 1.68; 95% CI: 1.00-2.48), had more than twofold increase in the risk of depression [78]. Persons with depression in diabetes have poorer cognition and higher dementia risk than those with only diabetes, as evidenced by the study of Chow et al [79]. They performed an observational meta-analysis on 10 studies from August 2015 to June 2021 (six years) on the adult population and found that persons with comorbid diabetes and depression had worse cognition (SMD: -0.77 (-1.33, -0.20)) and greater dementia risk (HR: 1.82 (1.79, 1.85)) than persons with only diabetes [79].…”
Section: Effect Of Depression On Morbidity and Mortality In Diabetesmentioning
confidence: 90%
“…Persons with depression in diabetes have poorer cognition and higher dementia risk than those with only diabetes, as evidenced by the study of Chow et al [79]. They performed an observational meta-analysis on 10 studies from August 2015 to June 2021 (six years) on the adult population and found that persons with comorbid diabetes and depression had worse cognition (SMD: -0.77 (-1.33, -0.20)) and greater dementia risk (HR: 1.82 (1.79, 1.85)) than persons with only diabetes [79]. Although these data cannot speak to causality, the consistency of findings linking depressive symptoms to poor diabetes health outcomes suggests that elevations should be seen as a marker of increased health risk; more longitudinal studies are needed to understand this causal relationship [35].…”
Section: Effect Of Depression On Morbidity and Mortality In Diabetesmentioning
confidence: 91%
“…Regarding sex differences, females (with and without diabetes) showed a higher prevalence of depression than males. Further, regarding the relationships between diabetes, depression, and dementia, a systematic review was conducted over 6 years [25]. The protocol included Embase, PubMed, and PsycINFO, and 10 articles from 19 papers were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Low BDNF levels are present in dementia patients[ 18 , 19 ] and patients with T2D are approximately two to four times more likely to develop dementia than individuals without T2D. These associations might explain why T2D, depression and dementia are often associated in the same patient[ 20 - 23 ]. We are aware that these are hypotheses, but we can consider them as useful reflections inspired by the article by Porter and O’Connor[ 1 ] to be validated in future studies.…”
Section: To the Editormentioning
confidence: 99%